2010
DOI: 10.3109/00048670903487118
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatology and Neuropsychological Functioning in Cannabis Using Subjects at Ultra-High Risk for Developing Psychosis and Healthy Controls

Abstract: Cannabis-using UHR patients have more basic symptoms than non-using patients. In addition, healthy cannabis users have more subclinical UHR and basic symptoms and more neuropsychological dysfunctions than non-cannabis users. More frequent cannabis use was related to increased severity of certain UHR symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 23 publications
5
47
2
2
Order By: Relevance
“…Executive function impairments including working memory (WM) [39][40][41][42][43][44][45][46][47], spatial memory and verbal fluency deficits [48][49][50][51][52][53][54][55], and reward and salience processing anomalies [56][57][58][59] are pronounced cognitive features found in schizophrenia. However, the relation of physiological and clinical variables (positive, negative symptoms) is complicated by the multidimensional nature of psychotic symptoms.…”
Section: Neuroimaging Findings In Psychosismentioning
confidence: 99%
“…Executive function impairments including working memory (WM) [39][40][41][42][43][44][45][46][47], spatial memory and verbal fluency deficits [48][49][50][51][52][53][54][55], and reward and salience processing anomalies [56][57][58][59] are pronounced cognitive features found in schizophrenia. However, the relation of physiological and clinical variables (positive, negative symptoms) is complicated by the multidimensional nature of psychotic symptoms.…”
Section: Neuroimaging Findings In Psychosismentioning
confidence: 99%
“…Third, little is known about the change in substance use over time in this population. Fourth, in studies examining the substance use-transition to psychosis link, some recorded patterns of cannabis use only (Korver et al 2010) whereas other studies grouped the use of any substance into one variable (Cannon et al 2008; Thompson et al 2011). Fifth, studies that reported on smaller sample sizes may be underpowered to detect an effect of substance use on transition to psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, studies that reported on smaller sample sizes may be underpowered to detect an effect of substance use on transition to psychosis. Further details on cannabis use in particular also deserve further evaluation as there are some results suggesting that cannabis use may be related to severity of attenuated psychotic symptoms (Corcoran et al 2008;Korver et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Recent reviews suggest that marijuana is a partial causal factor. 11 The association between marijuana use and the onset of psychosis is stronger for people with a predisposition for psychotic disorders. Onset of use before the age of 16 has a much stronger effect than if the cannabis use started at a later age.…”
mentioning
confidence: 99%
“…Onset of use before the age of 16 has a much stronger effect than if the cannabis use started at a later age. 11 It can be concluded that early marijuana use is a risk modifying factor for psychosis related outcomes. 9 There is an emerging body of evidence that suggests that the early stage of schizophrenia might provide an opportunity for interventions, even very simple ones that may help to prevent the development of full blown schizophrenia.…”
mentioning
confidence: 99%